The very true legend of the Mongolian death worms - Fay, Sandra (Henry Holt and Copmany, 2021)
"Meet the Mongolian death worm family: Beverly, Trevor, Neville, and Kevin. In spite of their deadly reputation, they're determined to make friends with the other animals. The other animals are not so eager...But when disaster strikes, it's the Mongolian death worm family to the rescue in this funny and charming debut picture book!"--